Effect of nostalgia as a motivational force for depressed students to seek professional psychological help. Issue 2 (8th March 2022) - Hussain, Syed Ali; Alhabash, Saleem
Abstract: In times of distress, people show a tendency to remember the 'good old days, ' a bittersweet emotion called Nostalgia. This study explores how experimentally-induced nostalgia improves attitude toward counseling center and behavioral intentions to contact the counseling center on a college campus. Students living with depression ( N  = 148) were randomly assigned to view a public service announcement (PSA) for the campus counseling center that was designed with or without a nostalgia-inducing narrative and imagery. Participants exposed to the nostalgic PSA expressed significantly higher positive emotions compared to the control condition, after controlling for the effects of stigma, past counseling experience, levels of depression, and friends or family with mental illness. Mediation analyses showed that the higher positive emotions participants felt, the more positive was their attitude toward the campus counseling center, which in turn increased behavioral intention to seek help. The study suggests nostalgia-themed messages to promote help-seeking intentions among students experiencing depression.